2019
DOI: 10.3390/ma12030550
|View full text |Cite
|
Sign up to set email alerts
|

Copper/Epoxy Joints in Printed Circuit Boards: Manufacturing and Interfacial Failure Mechanisms

Abstract: Printed circuit boards (PCBs) have a wide range of applications in electronics where they are used for electric signal transfer. For a multilayer build-up, thin copper foils are alternated with epoxy-based prepregs and laminated to each other. Adhesion between copper and epoxy composites is achieved by technologies based on mechanical interlocking or chemical bonding, however for future development, the understanding of failure mechanisms between these materials is of high importance. In literature, various in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 102 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…The deposit volume V p was calculated from the averaged d(r) data by numerical integration of the product, d(r) × 2πr over r, in the limits from r = 0 to an upper value r max , where d(r max ) was virtually zero. In certain regions, d may be in error by Weak adhesion strength of copper/epoxy joints, for example, in printed circuit boards, has been an issue for decades, see, for example, the review reported in Nothdurft et al [42]…”
Section: Instrumentationmentioning
confidence: 99%
“…The deposit volume V p was calculated from the averaged d(r) data by numerical integration of the product, d(r) × 2πr over r, in the limits from r = 0 to an upper value r max , where d(r max ) was virtually zero. In certain regions, d may be in error by Weak adhesion strength of copper/epoxy joints, for example, in printed circuit boards, has been an issue for decades, see, for example, the review reported in Nothdurft et al [42]…”
Section: Instrumentationmentioning
confidence: 99%
“…48 Chemical information at the interfaces between the metal materials and coating/packaging polymers in FPCs and other microelectronics parts is critical in terms of adhesion, mechanical strength, and insulation, and there is a great need for this analysis. 4952…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion between epoxy resin and metals is of great relevance in diverse industry sectors, such as automotive, aerospace, energy, and electronics [ 1 , 2 , 3 ]. Particularly, the fabrication of metal/epoxy/metal joints and metal/epoxy coatings usually requires a previous treatment of the metal surface in order to achieve good adhesion strength.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting improvement of the copper/epoxy adhesion strength has been attributed to the nucleation of acicular CuO crystals on top of the Cu 2 O layer [ 4 ]. However, the Cu/epoxy bonds prepared using this protocol present some drawbacks, such as their poor durability in acidic environments [ 1 , 4 ] due to corrosion of the oxide, causing delamination problems. The use of aggressive agents in chemical treatments may create a large volume of hazardous and contaminant wastes that can negatively affect natural environment and human health.…”
Section: Introductionmentioning
confidence: 99%